2020
DOI: 10.1021/acs.energyfuels.0c01596
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Interfacial Behavior of Surfactants and Asphaltenes: Molecular Dynamics Simulation Study

Abstract: Heavy oil and bitumen drive the leading energy supply in Canada. Several techniques, including in situ thermal methods and mining, have been applied to the recovery of these unconventional resources. Nowadays, to improve the efficiency of in situ thermal methods, coinjection of steam and different types of additives, including chemicals, solvents, and noncondensable gases, is being investigated. Adding these additives to steam can reduce the required amount of steam and, as a result, lowers carbon dioxide emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 100 publications
0
30
0
Order By: Relevance
“…Figure 5 demonstrates changes of RDF curves between asphaltene and other components before and after adding the light distillate oil, which can be used to figure out the influence of light components on other fractions in the heavy fuel oil. According to previous research, the maximum hydrogen bonds length is 2.5Å, as no peak is found at a distance lower than 2.5Å in heavy fuel oil and low-sulfur fuel oil RDF curves, so hydrogen bond does not exist in both models [53].…”
Section: Radial Distribution Function (Rdf)mentioning
confidence: 79%
“…Figure 5 demonstrates changes of RDF curves between asphaltene and other components before and after adding the light distillate oil, which can be used to figure out the influence of light components on other fractions in the heavy fuel oil. According to previous research, the maximum hydrogen bonds length is 2.5Å, as no peak is found at a distance lower than 2.5Å in heavy fuel oil and low-sulfur fuel oil RDF curves, so hydrogen bond does not exist in both models [53].…”
Section: Radial Distribution Function (Rdf)mentioning
confidence: 79%
“…E bond represents the potential energy of the bond length between two bonded atoms due to deformation, E angle represents the potential energy of the formation of two consecutive chemical bonds between three bonded atoms due to angular motion, and E torsion represents the potential energy of four atoms due to torsion. Ahmadi and Chen [24] carried out MD simulations to preliminarily study the interfacial behavior of asphaltene and surfactant in aqueous solution. The results showed that the interaction between anionic surfactant and asphaltene was greater than that of other surfactants.…”
Section: Research On Stable Foammentioning
confidence: 99%
“…Some studies have addressed the interactions of maltenes and asphaltenes by density functional theory [ 39 , 40 , 41 ] and molecular dynamics simulations [ 42 , 43 ], and experimental studies have investigated the aggregation ability of asphaltenes in different solvents [ 44 , 45 , 46 ]. Although some of these studies found evidence of a stronger interaction between asphaltenes and aromatic molecules, the aromatic–aromatic interactions do not appear to be exclusively responsible for the asphaltene–maltene interactions, as strong anionic, polar and acid-base interactions were also found.…”
Section: Theorymentioning
confidence: 99%